Generating two-spin squeezed states of separated Bose-Einstein condensates (2020)
ABSTRACT: We theoretically study a scheme for generating squeezing between two Bose-Einstein condensates (BECs). The scheme involves placing two BECs in the path of a Mach-Zehnder interferometer, where the coherent light interacts with the atoms due to the ac Stark shift. The most relevant regime for producing squeezing is in the short time regime, defined as when the interaction time scales as the inverse square root of the atom number. In this regime it is possible to construct a very simple approximate theory for the overall effect of the scheme: amplitudes in the superposition between the two BECs with unequal spin eigenvalues are damped. We analyze the types of correlations, entanglement, Einstein-Podolsky-Rosen (EPR) steering, and Bell correlations that are produced and show that the state is similar to a spin-EPR state. Using a two-pulse sequence the correlations can be dramatically improved, where the state further approaches a spin-EPR state.